Writing “things ecclesiastical”: the literary Acts of the gathered Churches - Anne Dunan-Page (Etudes Epistémè)
The activities of the dissenting, gathered Churches, constituted by small groups of so-called “visible” saints, are best known through the pamphlet and polemical literature of the Civil War and the Restoration. In County Record Offices, in libraries, and even in private hands, there is an important and largely unexploited body of manuscript Church books that testify to the vitality of dissenting literature. These manuscripts are often considered, albeit mistakenly, as “Church records” or “Church minutes” recording the debates of the monthly meetings; in fact, they encompass an astonishing variety of genres including letters, spiritual testaments, biographies, autobiographies and narratives of controversies. They can be seen as acts of faith, meant to build “monuments” to divine Providence, and they are fundamental sources for the history of dissent. They follow a range of literary models, from the Acts of the Apostles to Foxe’s Actes and Monuments. They call for a reassessment of Congregational literature, for it is a site of conflict between competing discourses and between personal as opposed to collective acts of writing.